PRAKTIK TRANSFER PRICING DITINJAU DARI SISI AKUNTANSI DAN PERPAJAKAN INDONESIA (Fokus Ekonomi, 2010)
Price of main product or service that has been transferred on main profit in a business is included of transfer pricing. From Government side, transfer pricing is curtained effecting decreased or lost of revenue tax profit a country, because multinational enterprise inclined to remove taxation obligation. While from business side, transfer pricing is believed as accurate strategy that the most effective that its used a lot of enterprises to win the business competition. The key to a successful practice of transfer pricing from tax standpoint is the existence of related parties transactions. Transferring price is set by virtue of arm’s length. Arm’s length is hard adapted so it occurred pro and contra between tax obligation and fiscus. On transfer pricing both of government and others enterprise can use OECD Transfer Pricing Guidelines, Advance Pricing Agreement, and P3B as orientations besides General Director Tax decision KEP-01/PJ.7/1993 and Circular of General Director Tax N0. SE-04/PJ.7/1993 dated March, 03, 1993